Facile and Promising Method for Michael Addition of Indole and Pyrrole to Electron-Deficient trans-β-Nitroolefins Catalyzed by a Hydrogen Bond Donor Catalyst Feist’s Acid and Preliminary Study of Antimicrobial Activity - Abdullah M. A. Al Majid; Mohammad Shahidul Islam; Assem Barakat; Mohamed H. M. Al-Agamy; Mu. Naushad (The Scientific World Journal)
The importance of cooperative hydrogen-bonding effects has been demonstrated using novel 3-methylenecyclopropane-1,2-dicarboxylic acid (Feist’s acid (FA)) as hydrogen bond donor catalysts for the addition of indole and pyrrole to trans-β-nitrostyrene derivatives. Because of the hydrogen bond donor (HBD) ability, Feist’s acid (FA) has been introduced as a new class of hydrogen bond donor catalysts for the activation of nitroolefin towards nucleophilic substitution reaction. It has effectively catalyzed the Michael addition of indoles and pyrrole to β-nitroolefins under optimum reaction condition to furnish the corresponding Michael adducts in good to excellent yields (up to 98%). The method is general, atom-economical, convenient, and eco-friendly and could provide excellent yields and regioselectivities. Some newly synthesized compounds were for examined in vitro antimicrobial activity and their preliminary results are reported.